Disclosure, reporting and help seeking among child survivors of violence: A cross-country analysis - Pereira, Audrey; Peterman, Amber; Neijhoft, Anastasia Naomi; Buluma, Robert; Daban, Rocio Aznar (BioMed Central, 2020)
Violence against children is a pervasive public health issue, with limited data available across multiple contexts. This study explores the rarely studied prevalence and dynamics around disclosure, reporting and help-seeking behaviours of children who ever experienced physical and/or sexual violence.